2020
DOI: 10.3758/s13423-020-01835-3
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent memory effects in two immersive virtual reality environments: On Mars and underwater

Abstract: The context-dependent memory effect, in which memory for an item is better when the retrieval context matches the original learning context, has proved to be difficult to reproduce in a laboratory setting. In an effort to identify a set of features that generate a robust context-dependent memory effect, we developed a paradigm in virtual reality using two semantically distinct virtual contexts: underwater and Mars environments, each with a separate body of knowledge (schema) associated with it. We show that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…The more vivid the retrieved memory is, the better effect of intervention during the reconsolidation should be. A prominent advantage of VR in memory reactivation is the sense of presence generated by interactive, diverse cues presented in immersive and vivid scenarios ( 95 , 96 ). MA-dependent patients are more likely to re-experience their drug-related episodic memories and generate MA cravings encountering drug-related cues and context in VR ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…The more vivid the retrieved memory is, the better effect of intervention during the reconsolidation should be. A prominent advantage of VR in memory reactivation is the sense of presence generated by interactive, diverse cues presented in immersive and vivid scenarios ( 95 , 96 ). MA-dependent patients are more likely to re-experience their drug-related episodic memories and generate MA cravings encountering drug-related cues and context in VR ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent work has shown that the relevance of an environmental context to the information being learnt in that context is consequential for that information's memorability. 17 In our task the relationship of the contexts to the languages and vocabulary being learnt was completely arbitrary. Future studies may confer memory advantages if language learning occurs in VR-based replicas of familiar real-world environments where that language would actually be useful (e.g., learning fruit vocabulary while navigating through the produce section of a grocery store).…”
Section: Discussionmentioning
confidence: 99%
“…15 Virtual reality (VR) offers a powerful means to create immersive learning environments that are highly distinctive and well-controlled, in order to examine and exploit context-based memory modulation. 15,16 Indeed, one recent study used two distinctive VR-based contexts-one underwater and one on the surface of Mars 17 -to conceptually replicate Godden & Baddeley's classic finding of context-dependent recall. When using VR environments as contexts, it is valuable to measure participants' sense of presence, [18][19][20][21] which refers to their sense of experiencing a VR-based environment as a place that one has actually inhabited, rather than something that one was merely watching passively (e.g., "I feel like I am in this space station, walking around," vs "I am watching this space station on a screen while sitting in a lab.").…”
Section: Introductionmentioning
confidence: 99%
“…The classical contextual dependence of memory describes the phenomenon that retrieving information is easier in the same extrinsic context as it was encoded (Cairney et al, 2011;Godden & Baddeley, 1975;McKenzie & Tiberghien, 2004;Smith, 1979;Smith et al, 1978). The pioneering work of Godden & Baddeley (1975), tested memories in two extremely different contexts (divers learned on dry land and underwater) and showed significantly better memory at recall when the external context of encoding and recall was the same (for recent replication attempts, see Murre, 2021;Shin et al, 2021). Smith (1979) worked on the question whether the familiarity of a context rather than the learning occurring in that context improved retrieval.…”
Section: Introductionmentioning
confidence: 99%